2012
DOI: 10.1371/journal.pone.0042822
|View full text |Cite
|
Sign up to set email alerts
|

The Human EKC/KEOPS Complex Is Recruited to Cullin2 Ubiquitin Ligases by the Human Tumour Antigen PRAME

Abstract: The human tumour antigen PRAME (preferentially expressed antigen in melanoma) is frequently overexpressed during oncogenesis, and high PRAME levels are associated with poor clinical outcome in a variety of cancers. However, the molecular pathways in which PRAME is implicated are not well understood. We recently characterized PRAME as a BC-box subunit of a Cullin2-based E3 ubiquitin ligase. In this study, we mined the PRAME interactome to a deeper level and identified specific interactions with OSGEP and LAGE3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 35 publications
(72 reference statements)
1
44
0
Order By: Relevance
“…The N 6 -threonylcarbamoyladenosine (t 6 A) modification is required for normal cell growth and accurate protein translation in bacteria, archaea, and eukaryotes. While the bacterial and lower eukaryotic components of the EKC/KEOPS complex are known, some of the human subunits are substantially diverged and have only recently been discovered [61, 62]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N 6 -threonylcarbamoyladenosine (t 6 A) modification is required for normal cell growth and accurate protein translation in bacteria, archaea, and eukaryotes. While the bacterial and lower eukaryotic components of the EKC/KEOPS complex are known, some of the human subunits are substantially diverged and have only recently been discovered [61, 62]. …”
Section: Resultsmentioning
confidence: 99%
“…Clear orthologs of four of these occur in humans and have previously been confirmed to participate in the EKC/KEOPS complex: TP53RK (the ortholog of Bud32, known to partially complement a Bud32 mutant [63]), TPRKB (the ortholog of Cgi121), LAGE3 (the ortholog of Pcc1), and OSGEP (the ortholog of Kae1). The yeast Gon7 has generally been thought to be fungi-specific [59, 61], and has no clear mammalian ortholog in major ortholog databases [36, 64]. …”
Section: Resultsmentioning
confidence: 99%
“…The epitope tag (TY1-TY1-ER) had already been successfully used for IP and ChIP applications [25] and was placed at the N-terminus of the protein. TTE-MBD2 expressed in MCF-7 cells is specifically recognized by the Ty1 antibody (Fig1B left panel), that does not detect the endogenous protein in wild type MCF-7 cells (WT).…”
Section: Resultsmentioning
confidence: 99%
“…Costessi et al (2011, 2012) reported that PRAME is a component of Cullin2 based E3 ubiquitin ligase and is required to recruit Cullin2 ubiquitin ligase to the EKC/KEOPS complex. This complex is associated with the active promoters regulated by the nuclear transcription factor Y ( NFY ) [29], [32]. We hypothesize that PRAME also plays a role in spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%